Sanksi Pidana Terhadap Pencemaran Tukad Unda Dalam Kegiatan Pengerukan Tanah Pembangunan Pusat Kebudayaan Bali (PKB) - I Gede Agus Allezandro Suputra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Warmadewa Press, 2025)
Law No. 32 of 2009 explains that Natural contamination causes harm to biotic and abiotic communities. Natural contamination issues happening are natural issues due to the digging of slopes and waterways around the Unda Waterway which can be utilized as materials for development objects. In case not dealt with genuinely, this huge sum of digging will influence the condition of the encompassing environment. The details of the issue are: How are criminal sanctions controlled for culprits of Unda Stream contamination due to slope digging amid the development of the Bali Social Center? and How is the Tukad Unda stream overseen and secured? About employment standardizing legitimate investigation strategies. Setting criminal sanctions against culprits of waterway digging contamination is critical to energize lawful compliance and natural security. sanctions can be within the shape of fines, jail sentences, or combination of both, duty of the culprit and give obstruction impact against waterway contamination homes. Stream stream administration and assurance requires an all encompassing approach including related parties, compelling directions and community support. Usage of preservation measures, coordination between related teaching, outreach to open almost all threats postured by exercises carried out in waterway watersheds, as well giving strict sanctions for infringement of the utilization of watersheds as ensured zones.